Abnormal grain growth in Fe–Mn–Al–Ni shape memory alloy with higher Al content. (October 2020) - Xia, Ji; Omori, Toshihiro; Kainuma, Ryosuke
Abstract: The effect of Al content on the abnormal grain growth of Fe–Mn–Al–Ni shape memory alloy is investigated in comparison with the previously reported Fe–Mn–Al–Ni–Ti alloy. Microstructural observations revealed that compared with 1.5Ti, 17Al (adding 2 at.% Al to the conventional Fe–Mn–Al–Ni) showed the potential to grow into a large single crystal. The obtained results indicate that the size control of the second phase, which can be achieved not only by introducing Ti, but rather universally by stabilizing BCC phase, and the resultant subgrain structure are vital for abnormal grain growth. Graphical abstract: Image, graphical abstract